Influence costs and hierarchy - Roman Inderst; Holger M. Müller; Karl Wärneryd (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
In an internal capital market, individual departments may compete for a share of the firm's budget by engaging in wasteful influence activities. We show that firms with more levels of hierarchy may experience lower influence costs than less hierarchical firms, even though the former provide more opportunities for exerting influence. We further argue that the widely discussed change from the U-form to the M-form organization in the 1920s may be related to attempts to limit divisional lobbying. In particular, we show that influence costs under the U-form organization are lower than under the M-form organization if and only if the firm's operations are sufficiently small.
Keywords: D74; G31; G34; 330; Hierarchies; influence activities; internal capital markets; U-form vs. M-form organization